(untitled) (La Rivada, 2024)
Death is, like almost no other human event, a privileged object of study of collective representations. It is a social and cultural issue that redefines and challenges not only the group that goes through it but also operates on individual subjectivity. The ways of dealing with finitude also reflect the society where it develops, establishing the emotional regime appropriate at that historical moment. As part of a line of research started in 2014, and based on numerous interviews to Korean migrants and their descendants in the Autonomous City of Buenos Aires, we are interested in delving into the ways in which they carry out their funeral rituals against the background of migratory trajectory and where references to their country of origin are recurrent. To deepen our analysis, we also look into the website of the Agency for the Promotion of Funeral Culture in Korea, set up/created by the Ministry of Health and Welfare in 2013, which provides extensive information regarding all relevant aspects. linked. This has raised the question of whether, within the backdrop of K-wave, death, as another product, is presented in Korean drama series. If so, within this aesthetic framework, we aim to identify (the main?) themes and settings associated with funerary practices and its performativity (its rituals) in order to record the ways in which death and its rituality are (re-)presented and re-imagined.